Severe Acute Respiratory Syndrome Coronavirus 2 Evolution and Escape From Combination Monoclonal Antibody Treatment in a Person With HIV - Khosravi, Dara; Soloff, Hannah; Langsjoen, Rose M; Bombin, Andrei; Kelley, Colleen F; Ray, Susan M; Gunthel, Clifford J; Zanoni, Brian C; Nguyen, Phuong-Vi; Waggoner, Jesse J; Wang, Yun F; Cantos, Valeria D; et al. (Open forum infectious diseases, 2023)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) escape from combination monoclonal antibody treatment is rarely reported. We describe an immunocompromised individual with human immunodeficiency virus and persistent SARS-CoV-2 infection in whom substantial SARS-CoV-2 evolution occurred, including the emergence of 2 mutations associated with escape from the monoclonal antibody cocktail received.